Pengaruh Latihan Small Side Game melalui Phyramid Method terhadap Peningkatan Kapasitas An-Aerobic Laktasid (Jurnal Simki Pedagogia, 2025)
This study used an experimental design with a pre-experimental approach. The subjects of the study were Persib Academy athletes aged 17-18 years, totaling 50 people. The researcher conducted a pre-observation with an anaerobic lactase test. The results of the initial observation showed that 10 athletes had low anaerobic lactase levels, so the number of samples in this study was set at 10 people using a purposive sampling technique. Measurement of anaerobic lactase capacity was carried out before and after the intervention using a 150-meter sprint test. Data were analyzed using inferential statistical tests with a t-test at a significance level of 5% to determine the significance of the changes. The results showed a significant increase in the anaerobic lactase capacity of respondents, as measured by the 150-meter sprint test and post-exercise lactic acid levels. The significance value (sig. 2-tailed) of 0.032